Determinants of skilled birth attendants in Nepal: a case of Surkhet district - Shah, Sunil; Simoes, Jose Augusto R. (International Journal Of Community Medicine And Public Health, 2022)
Background: Safe delivery incentive program was introduced to increase the skilled attendants at births. The program provided childbirth by skilled birth attendants as well as incentives to skilled birth attendants ‘cash’ to women giving birth in a health facility in addition to incentives to health provider for each delivery attended, either at home or the facility. Due to its implementation and administrative delays, the program was reformed and implemented as a ‘safer mother program’ popularly known as “aama-suraksha-karyakram” since January 2009. Methods: The study was conducted in Surkhet district of Nepal. Surkhet is a hilly district and is head-quarter of mid-western development region of Nepal. There is one hospital, 5 PHCCs, 9 HPs and 38 SHPs serving 288,527 people in the district. The delivery by trained health worker (HW) in the district is 31.8% in 2005/06 which has increased about two times for two years. Surkhet is one of the districts monitoring the process indicators for safe motherhood programme in Nepal. Birth preparedness package programme has been implementing in the district from this year. The study population were the mothers within the age group of 15 to 49 years in Surkhet district. The sampling frame of the study was the mothers who had delivered the baby within 12 months preceding the survey. Results: About one third mothers, having 0-5 poverty score, utilised delivery assisted by HWs, while about three fourth of them having more than 5 score utilised HWs as delivery assistant. Higher educated mothers utilised HWs as delivery assistant more than that of higher educated husband. Among higher educated mothers, about 85% utilised delivery assisted by HWs, while it was about 75% for higher educated husband. Occupation of mother was also significantly associated with utilisation of delivery by HWs. Mother having office work utilised about 5 times higher HWs than others as their delivery assistant. The distance to health facility was significantly associated with utilisation of delivery attendant (p value <0.001). The mothers with less travelling time to reach health facility were more likely to utilise HWs as delivery attendant. About three fourth mothers who needed less than half an hour utilised delivery assisted by HWs. There was equal proportion of mothers who needed 30-59 minutes to reach the nearest health facility. In the other hand, about 73% of mothers who needed one hour or more to reach health facility utilised others as delivery assistant. Perceived quality of service to nearby health facility by mothers was also significantly associated with utilisation of HWs as delivery attendant (p value <0.05). About two third of mothers perceiving good quality of service at local health facility utilised HWs as delivery attendant while, it was only 44% among mothers perceiving poor quality of services. Conclusions: There should be adequate planning and preparation at all levels of health facilities; implementing a new program should not adversely affect another existing service delivery system. For the optional implementation, hospital organogram should be revised; and physical facilities and the low-risk birthing-centers with referral linkages should be expanded.